Carbon based nanomaterials for advanced thermal and electrochemical energy storage and conversion - Paul, Rajib; Etacheri, Vinodkumar; Wang, Yan; Lin, Cheng-Te (Micro and nano technologies series, 2019)
"Carbon Based Nanomaterials for Advanced Thermal and Electrochemical Energy Storage and Conversion presents a comprehensive overview of recent theoretical and experimental developments and prospects on carbon-based nanomaterials for thermal, solar and electrochemical energy conversion, along with their storage applications for both laboratory and industrial perspectives. Large growth in human populations has led to seminal growth in global energy consumption, hence fossil fuel usage has increased, as have unwanted greenhouse gases, including carbon dioxide, which results in critical environmental concerns. This book discusses this growing problem, aligning carbon nanomaterials as a solution because of their structural diversity and electronic, thermal and mechanical properties"--